Hybrid equivalent source – 3D ray-launching simulation technique for deterministic estimation of radiated emissions of electrical appliances. Issue 4 (3rd March 2016) - López-Iturri, P.; Rodríguez-Ulibarri, P.; Aguirre, E.; Azpilicueta, L.; Beruete, M.; Falcone, F.
Abstract: In this work, a method for modeling the leaked radiofrequency radiation from electrical appliances is presented, with the aim of obtaining a model for a 3D ray-launching algorithm. The domestic microwave oven is the appliance under analysis, as it radiates a substantial amount of power and it is spread worldwide. The method uses numerical electromagnetic field simulations to obtain the exterior oven radiation. Due to the complexity of the metallic mesh of the oven door, a retrieval process has been implemented in order to accelerate the electromagnetic field simulation. This result is incorporated to a proprietary 3D ray-launching algorithm by obtaining equivalent radiation sources. Finally, the microwave oven leakage is obtained for the complete volume of an indoor scenario. The numerical results are then compared with experimental measurements, with good agreement. The proposed model is useful to predict accurately the leakage of the domestic microwave oven within a complete complex indoor scenario, aiding in further radioplanning considerations.